KOMUNIKASI ORGANISASI DALAM PEMERTAHANAN EKSISTENSI PIMPINAN CABANG KESATUAN MAHASISWA HINDU DHARMA INDONESIA DENPASAR - I Made Dwipo Darma Yasa,; I Wayan Suwadnyana,; I Nyoman Surpa Adisastra, (Journal of Innovation Research and Knowledge, 2026)
It is evident that organisational communication assumes a pivotal role in the context of sustaining and preserving the very existence of an organisation, a fact that is equally applicable to student organisations. One such entity is a student organisation that perpetuates its existence through the medium of communication facilitated by PC KMHDI. The present study will discuss how the organisational communication of the Branch Leadership of the Indonesian Hindu Dharma Student Union (PC KMHDI) Denpasar maintains the existence of the organisation, identifies communication barriers that occur, and analyses the implications of organisational communication on the existence of PC KMHDI Denpasar. The present study employs a qualitative approach, utilising a descriptive method. The data collection techniques employed in this study encompass in-depth interviews, observational studies, and document analysis. The purposive selection of research informants involved administrators and members of PC KMHDI Denpasar. The analysis of data is conducted through three distinct stages: data reduction, data presentation, and conclusion drawing. The results of the study indicate that organisational communication of PC KMHDI Denpasar is carried out through formal and informal communication by utilising digital and face-to-face communication media. The role of organisational communication in maintaining the existence of the organisation is threefold: firstly, it delivers information; secondly, it coordinates activities; and thirdly, it builds member involvement. Nevertheless, organisational communication continues to encounter technical, semantic and behavioural impediments that impede the efficacy of message delivery. The implications of organisational communication for the existence of PC KMHDI Denpasar are evident in the cognitive aspect, which is members' understanding of the organisation; the affective aspect, which is the emotional attachment of some members; and the behavioural aspect, which is members' actual involvement in organisational activities, although this is not yet evenly distributed.